Pengaruh Doping Cu terhadap Karakteristik Material dan Ketahanan Karbon pada Anoda Ni1-X-CuX-BCZY untuk PSOFC - Setiawan, Nanang; Tseng, Chung-Jen; Shen, Chin Tien; Wardana, ING (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
The purpose of this study is to investigate the microstructure characteristics of the Ni1-xCux-BCZY anode and to analyze the carbon resistance by doping Cu into the Ni-BCZY anode. Ni1-xCux and BaCe0.7Zr0.1Y0.2O3-ð›¿ (BCZY) powder were prepared by solid-state reaction with Ni1-xCux /BCZY = 60:40 wt%. The powder is calcined at a temperature of 700 Â°C, sintered at 1450 Â°C, and reduced by pure H2. The results of the Ni1-xCux-BCZY microstructure show an increase in the average particle size from 2.71 to 2.88 Âµm with increasing calcination time from 0.5 to 1.5 hours. Furthermore, the conductivity of Ni1-xCux-BCZY (x = 0.1) is lower than Ni1-xCux-BCZY (x = 0), this is associated with enhancement electron scattering, which correlatives with large metal particle obtained. The optimum conductivity of Ni1-xCux-BCZY(x=0.1) is obtained at a calcination time of 0.5 hours. Furthermore, NiCu anode can effectively increase the carbon resistance while using methane as a fuel.